2014
DOI: 10.1088/0004-637x/782/1/2
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION OF ℓ = 4 AND ℓ = 5 MODES IN 12 YEARS OF SOLAR VIRGO-SPM DATA—TESTS ONKEPLEROBSERVATIONS OF 16 Cyg A AND B

Abstract: We present the detection of = 4 and = 5 modes in power spectra of the Sun, constructed from 12 yr full-disk VIRGO-SPM data sets. A method for enhancing the detectability of these modes in asteroseismic targets is presented and applied to Kepler data of the two solar analogues 16 Cyg A and B. For these targets we see indications of a signal from = 4 modes, while nothing is yet seen for = 5 modes. We further simulate the power spectra of these stars and from this we estimate that it should indeed be possible to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 89 publications
5
21
0
Order By: Relevance
“…The value found for the solar ν max of 3078 ± 13 µHz is in agreement with the value of ν max, = 3090 ± 30 µHz by Huber et al (2011). We obtained ∆ν and from a fit to the extracted mode frequencies with an extended version of the asymptotic relation, as in Lund et al (2014a) (see also Mosser et al 2011Mosser et al , 2013. This fit was made in a Bayesian manner using emcee, with a likelihood function assuming Gaussian frequency errors, and with final parameter values and uncertainties given by the posterior medians and HPDs.…”
Section: Average Seismic Parameterssupporting
confidence: 84%
See 3 more Smart Citations
“…The value found for the solar ν max of 3078 ± 13 µHz is in agreement with the value of ν max, = 3090 ± 30 µHz by Huber et al (2011). We obtained ∆ν and from a fit to the extracted mode frequencies with an extended version of the asymptotic relation, as in Lund et al (2014a) (see also Mosser et al 2011Mosser et al , 2013. This fit was made in a Bayesian manner using emcee, with a likelihood function assuming Gaussian frequency errors, and with final parameter values and uncertainties given by the posterior medians and HPDs.…”
Section: Average Seismic Parameterssupporting
confidence: 84%
“…The comparisons do, however, qualitatively match those obtained by Mosser et al (2012) for giants observed by Kepler ; the l = 3 modes disagree most with theory in their results too. Similar discrepancies with theory have also been observed for individual CoRoT and Kepler targets analyzed by Deheuvels et al (2010), Mathur et al (2013), andLund et al (2014a), and the Sun by Salabert et al (2011). Given these discrepancies we discourage the adoption of fixed mode visibilities in peak-bagging exercises.…”
Section: Mode Visibilitiessupporting
confidence: 58%
See 2 more Smart Citations
“…This is because the fitting models do not usually account for the presence of "leakage" from = 4 and 5 into the fitting window (as we also omitted to do it here), although they can be measured in, for example, Sun-as-a-star observations using 12 years of VIRGO/SPM data (e.g. Lund et al 2014). …”
Section: Helioseismologymentioning
confidence: 99%